No time to dispose? a study on the correlations and its contributing factors affecting university students’ intention to practise e-waste / Muhamad Azfar Mohamad Zuhdi ... [et al.] - Mohamad Zuhdi, Muhamad Azfar; Rabun, Mohd Nazir; Hamdan, Haziq Iskandar; Ridzuan, Mohd Rozaimy (Universiti Teknologi MARA, Kedah, 2023)
E-waste is a serious environmental problem. This study examines the correlations and its contributing factors affecting the e-waste recycling intention level among university students. A cross-sectional design using a quantitative method was used in this research and out of 370 questionnaires distributed only 285 were useable for further analysis. Results showed that majority of the university students had an average level of e-waste recycling intention. The association between attitudes, environmental awareness, law and regulations, convenience of recycling facilities and service and e-waste recycling intention is significantly correlated with the e-waste recycling intention among university students. Findings showed that attitudes were the main factor affecting the e-waste recycling intention. Thus, this study contributes a greater understanding of e-waste recycling especially for university students as they are the educated community. As such, a proper e-waste recycling campaign is a collaborative effort to raise awareness on public as well as university students against the waste landing in landfills.